Influence of subaxial cervical spine surgery on the sagittal alignment of the cervical and global spine. A prospective observational study - M. Bolcha; J. Lodin; D. Cihlář; M. Sameš; P. Vachata (Brain and Spine)
Introduction: Sagittal balance is essential for posture, horizontal gaze and avoiding overloading the posterior segment of the spine. Research question: Does single- or double-level anterior cervical discectomy and fusion (ACDF) alter (1) cervical and global sagittal parameters and (2) outcomes in patients with kyphotic versus non-kyphotic alignment? Material and methods: In a prospective cohort, 103 adults underwent 1–2-level ACDF. Standing radiographs were obtained pre-operatively and 24 months post-operatively. Analysed were six cervical parameters, thoracolumbar curves and spinopelvic angles. Pain was rated on a Visual analogue scale and disability with the Neck Disability Index. Results: Kyphotic spines (n = 43) converted to lordosis (median ΔC2–C7 Cobb = +6.4°, CI 95 % 3,84-10,9) with concomitant reductions in C2–C7 SVA and rise in T1 slope (all p < 0.05); thoracolumbar and pelvic parameters were unchanged. Non-kyphotic spines (n = 60) showed no significant radiographic shifts. Both groups clinically improved: Kyphotic group VAS neck −2, VAS Arm −4 (p = 0,00037), non-kyphotic group VAS neck −3, VAS arm −3 (p = 0,00001) and clinical gains were independent of lordotisation magnitude. In the kyphotic group, the significant importance of the T1S-CL parameter was found. No reoperations, adjacent-segment disease or serious complications occurred. Discussion and conclusion: Single-/double-level ACDF affect local sagittal paramethers, correct kyphosis and modulates the cervicothoracic junction, but does not influence distal spinal or pelvic alignment. Pain relief and functional improvement are comparable in kyphotic and non-kyphotic patients, irrespective of relordotization magnitude. Patients may not require aggressive lordosis correction, based on their individual sagittal profiles. Nonetheless, these results and conclusions are limited to single-/double-level ACDFs.